Effect of solvent on the architectures of six Ag(I) coordination polymers based on flexible and quasi-flexible organic nitrogen donor ligands. (26th February 2016) - Yuan, Yuan; Xue, Xiao-Nan; Fan, Wei-Wei; Qiu, Qi-Ming; Cui, Yang-Zhe; Liu, Min; Li, Zhong-Feng; Jin, Qiong-Hua; Yang, Yu-Ping; Zhang, Zhen-Wei; Geng, Wen-Xiao; Zheng, Wen-Jie
Graphical abstract: Compounds1 –6 were fully characterized by IR, 1 H and 31 P NMR spectroscopy, elemental analysis, fluorescence, THz spectra and single-crystal X-ray crystallography. The crystal structures of complexes1 –2, 4 –6 consist of topological networks. In addition, complexes1 –6 exhibit interesting fluorescence in the solid state at room temperature. Abstract: The present work describes the synthesis, full characterization and architectural diversity of six new bioactive silver–organic networks, namely the coordination polymers [Ag(bpa)2 (CF3 SO3 )(H2 O)] n (1 ), [Ag2 (PPh3 )2 (bpa)2 ](CF3 SO3 ) n (2 ), [Ag(bpe)(CF3 SO3 )] n (3 ), [Ag(bpe)(CF3 SO3 )(CH3 CN)] n (4 ), [Ag(PPh3 )(μ-bpe)]1.5 (BF4 ) n (5 ) and [Ag(bpp)(CF3 SO3 )(CH3 CN)2 ] n (6 ), which are generated via a mixed-ligand strategy using 1, 2-bis(4-pyridyl)ethane (bpa), 1, 2-bis(4-pyridyl)ethene (bpe) or 1, 3-bis(4-pyridyl)propane (bpp) as the main building block and triphenylphosphine (PPh3 ) as an ancillary ligand source. Complexes1 –6 were well characterized by IR, 1 H and 31 P NMR spectroscopy, elemental analysis, fluorescence, THz spectroscopy and single-crystal X-ray crystallography. The complexes1, 2 and4 –6 have a topological network structure. The type and coordination modes of the bipyridine derivatives and the choice of solvent play a key role in defining the dimensionality as well as the structural and topological features of the resulting networks. Analysis of structures revealed that complex1 possesses a (5 4, 6 2 ) topological network structure connected through the bridging ligand bpa. Complex2 has a dinuclear structure and displays a topologically promising architecture connected through hydrogen bonds between the CH groups of aromatic ring and anions. Complexes3 and4 possess different 1D infinite chains which are linked by the bridging ligand bpe, and complex4 can be simplified as having a three-dimensional mesh topology. Complex5 has a (9 3, 3 3 ) topological network structure connected through the bridging ligand bpe. Like complex4, complex6 possesses 1D infinite chains through the bridging ligand bpp, which are linked by hydrogen bonds to form a 3D topological network. Complexes2 and4 are generated from CH2 Cl2 /CH3 OH (5:5) and CH3 CN respectively, while the other complexes are obtained from CH3 CN/H2 O (5:5). In addition, complexes1 –6 exhibit interesting fluorescence in the solid state at room temperature.